E4 Thematic Network Enhanging Engineering Education in Europe - Maffioli, Francesco; Borri, Claudio (Proceedings e report, 2004)
This Thematic Network aims at developing the European dimension of Higher Engineering Education by enhancing the compatibility of the many diverse routes to the profession of engineer, by facilitating greater mobility and integration of skilled personnel throughout Europe, by favouring a mutual exchange of skills and competences and providing a platform for communication between academics and professionals. Five main activities have been organised under the overall umbrella of the Thematic Network.The work contains 6 volumes.